Influence of Co‐Combustion of Alternative Derived Fuels on Air Emission from Cement Plants: Particulates and Trace Species. Issue 1 (2nd December 2015) - Richards, Glen; Agranovski, Igor E.
Abstract : As cement manufacturing is heavily intensive on material and energy requirements, its increasing demand for global production is set to double the industries current emission rates. With an increasing concern on public health from particulates and trace pollutants (particulate matter, metals, polycyclic aromatic hydrocarbons (PAHs), dioxins, polychlorinated bi‐phenyls (PCBs), and others)) opportunities to reduce emission levels (while sustaining the plants' required energy) require special attention. This paper presents an analysis on the air pollutant formation factors and subsequent unit mass emission factors (UMEFs) during the co‐combustion of alternative‐derived fuels (ADFs) in today's real‐world operating cement plants. Environmental emissions monitoring was conducted on ten cement batching plants while under normal and experimental operating conditions. In summary, the co‐combustion trials of ADFs have consistently shown to have minimal influence (or significant reduction) on the UMEF of particulates and trace pollutants. Some rather minor increase of pollutants' release was detected only for the following situations; usage of carbon dust and wood chips slightly increased concentration of total PAHs, waste solvents increased levels of chromium and dioxins, and tire‐derived fuel caused concentration increase of most metals and total PCBs. The co‐combustion of ADF substitute has identified the key process parameters contributing to contaminate suppression being (i) complete combustion; (ii) percentage of ADF substitution and firing rate; (iii) pre‐calciner fuel calorific value and firing rate, gas temperature, and material temperature; (iv) rotary kiln fuel calorific value and firing rate, flame temperature, and residence time, and the gas and material temperatures; and (v) fuel/air ratio. Abstract : Considering strong demand, global cement production rapidly grew and could potentially release elevated amounts of pollutants to the atmosphere. This paper is focused on experimental and theoretical analysis of air emissions from ten cement plants operated on traditional and alternative fuels. It was found that using alternative fuels does not contribute significantly to the air emissions and could be controlled by a number of process parameters.